Analisis Perbedaan Abnormal Return Dan Trading Volume Activity Sebelum Dan Sesudah Stock Split Pada Perusahaan Yang Melakukan Stock Split Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2017 - Nahdiyyah, Iim Rohimatun; Fujianti , Lisna Wulan (Ridwan Institute, 2025)
Stock split is one of the corporate activities used to increase stock liquidity. The main purpose of this study is to find out the difference between Abnormal Return and Trading Volume Activity before and after the announcement of the stock split. This study took a sample of 43 companies that conducted stock splits and were listed on the Indonesia Stock Exchange in the period 2015-2017. The sampling method used is purposive sampling. The research method has been carried out with a quantitative method, where the results can be obtained by calculating secondary data related to the research. The analysis method used in this study is the Wilcoxon Signed Rank Test with an observation window of t-5 (five days before the stock split) and t+5 (five days after the stock split). The results of the study show that the results of the Wilcoxon Signed Rank Test on the first hypothesis show that there is a difference in abnormal returns before and after the stock split, while the second hypothesis shows no difference in trading volume activity before and after the stock split.